2022
DOI: 10.1177/08404704221108466
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the use of technology in the long-term care sector in Canada: Insights from citizen panels and a national stakeholder dialogue

Abstract: Enhancing the use of technology in long-term care has been identified as a key part of broader efforts to strengthen the sector in the wake of the COVID-19 pandemic. To inform such efforts, we convened a series of citizen panels, followed by a national stakeholder dialogue with system leaders focused on reimagining the long-term care sector using technology. Key actions prioritized through the deliberations convened included: developing an innovation roadmap/agenda (including national standards and guidelines)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Although there is an emerging trend for developing innovation and technologies LTCHs, research showed that there is a mismatch between technology developed and the actual needs and preferences of residents (9). Moreover, technology might not be used or adequately adopted by staff in LTCHs (9). The sustainability of technology use remains a challenge in the eld.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is an emerging trend for developing innovation and technologies LTCHs, research showed that there is a mismatch between technology developed and the actual needs and preferences of residents (9). Moreover, technology might not be used or adequately adopted by staff in LTCHs (9). The sustainability of technology use remains a challenge in the eld.…”
Section: Introductionmentioning
confidence: 99%
“…To better deal with these challenges, long-term care organizations for older adults are investing time and budget in innovation [8][9][10][11][12]. Although long-term care organizations show great potential for innovation [12][13][14][15][16][17][18][19][20], many struggle to do this in a professional way [8][9][10]. Organizations that are innovation ready are more capable of implementing innovations [21][22][23].…”
mentioning
confidence: 99%